English language Teachers’ and EFL Students’ perceptions of oral errors and corrective feedback in a rural institution - Ahtziry Brindis Morales (Revista Lengua y Cultura)
This study explores the perception that English language teachers and students hold of errors and corrective feedback in oral communication. To collect data for this qualitative study semi-structured interviews were conducted with two English language teachers and five beginner English language students. The findings in this study provide evidence that teachers hold general knowledge about error correction and know how to provide corrective feedback. However, there may be factors that limit the implementation of corrective feedback in the workplace.  As regards the decision-making process about corrective feedback, students and teachers keep different perspectives